Review of the Efficacy and Safety of Dinoprostone “Insert”, “Gel”, and “Tablets” for Cervical Ripening and Induction of Labor - Yehia Elkhawly (17039088) (2023)
Introduction Cervical ripening and induction of labor are common obstetric interventions used to manage pregnancies that have reached or exceeded their due dates, have fetal or maternal complications, or for other medical reasons. Prostaglandins are commonly used for cervical ripening and induction of labor due to their ability to soften and efface the cervix, promote contractions, and facilitate vaginal delivery. Dinoprostone is a synthetic prostaglandin E2 analogue that is available in various formulations, including insert, gel, and tablets. However, there is limited research comparing the efficacy and safety of these different formulations. Methods We conducted a retrospective analysis of 181 women who underwent cervical ripening and induction of labor with dinoprostone insert (n=62), gel (n=76), or tablets (n=43) at our hospital. We collected data on patient characteristics, including age, body mass index (BMI), parity, gestational age, initial Bishop score, and indication for induction. Descriptive statistics, including means, standard deviations, and frequencies, were used to evaluate patient characteristics, change in Bishop score, complications, type of birth, time to vaginal delivery, and neonatal outcomes. Results The end bishop score was significantly higher in the insert group (8.32±2.24) compared to the gel (7.2±1.97) and tablet (6.72 ±1.25) groups. Fetal distress and maternal complications were low and similar among the three groups, except for tachysystole, which was more common in the insert group. The time to vaginal delivery was shortest in the tablet group (median=16 hours). Vaginal delivery was the most common mode of delivery in all three groups. Neonatal outcomes were similar among the three groups, except for a higher rate of NICU admission in the gel group. Conclusion The results of this study suggest that all three forms of dinoprostone are effective and safe for cervical ripening. However, the insert form showed a higher bishop score and a higher incidence of tachysystole, while the tablet form showed a shorter time to vaginal delivery. The gel form had a higher rate of NICU admission. These findings can help clinicians choose the most appropriate form of dinoprostone based on individual patient characteristics and preferences. Further prospective studies are needed to confirm these findings.